2018
DOI: 10.1007/s10344-018-1168-z
|View full text |Cite
|
Sign up to set email alerts
|

The NATURA 2000 database as a tool in the analysis of habitat selection at large scales: factors affecting the occurrence of pine and stone martens in Southern Europe

Abstract: Most studies on habitat selection among animals are conducted at local scales, whereas reliable determination of species requirements at larger spatial scales can be problematic. We used data available for NATURA 2000 sites to determine the habitat requirements of two relatively widespread and common species-pine marten Martes martes and stone marten Martes foina-in Southern Europe. Using presence-absence data, we applied statistical models at two spatial scales. At the local scale (within the dispersal distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…By combining Hutchinson's ecological niche and landscape connectivity, we assessed niche overlap between strictly related pine marten and stone marten and highlighted the role played by environmental factors in shaping their relative distribution in sympatry. With respect to previous studies (Vergara et al, ; Vergara, Cushman, Madeira, & Ruiz‐González, ; Wereszczuk & Zalewski, ; Zub et al, ), the inclusion in the models of human disturbance‐related variables enabled for the first time to define a possible mechanism, depending on circadian activity patterns, driving habitat partitioning in anthropogenically altered landscapes (and, potentially, also explaining pine marten dominance in forested habitats; Torretta et al, ). Interestingly, a similar pattern has been proposed to explain the distribution of archeological records of both martens in the second half of the Holocene (Llorente‐Rodríguez et al, ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…By combining Hutchinson's ecological niche and landscape connectivity, we assessed niche overlap between strictly related pine marten and stone marten and highlighted the role played by environmental factors in shaping their relative distribution in sympatry. With respect to previous studies (Vergara et al, ; Vergara, Cushman, Madeira, & Ruiz‐González, ; Wereszczuk & Zalewski, ; Zub et al, ), the inclusion in the models of human disturbance‐related variables enabled for the first time to define a possible mechanism, depending on circadian activity patterns, driving habitat partitioning in anthropogenically altered landscapes (and, potentially, also explaining pine marten dominance in forested habitats; Torretta et al, ). Interestingly, a similar pattern has been proposed to explain the distribution of archeological records of both martens in the second half of the Holocene (Llorente‐Rodríguez et al, ).…”
Section: Discussionmentioning
confidence: 95%
“…Although both the role of forested habitat as key features for martens and the avoidance of urban and open areas by the pine marten are well‐known behavioral patterns of these mustelids (review by Virgós et al, ; Vergara et al, ; Zub, Kozieł, Siłuch, Bednarczyk, & Zalewski, ), our analyses allowed to point out the effect of each species' tolerance toward human disturbance in shaping their relative patterns of distribution. What may be the origin of such different behavioral attitudes in these two prototypically similar (Larroque et al, ) species?…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 presents the variables used. Previous research has shown that climatic variables such as mean temperature and precipitation have no significant effect on the presence of martens (Zub, Kozieł, Siłuch, Bednarczyk, & Zalewski, 2018). Although such clear evidence is not available for squirrels, the relatively homogeneous, mild climatic conditions of Northern Ireland and absence of extreme weather events (McCarthy, Gleeson, & Walsh, 2015; Peel, Finlayson, & McMahon, 2007) would suggest that environmental effects within the region on the species occurrence are minimal.…”
Section: Methodsmentioning
confidence: 97%
“…), p (covariate)). Next, we used the best fitting model for detection probabilities and combined it with a set of a priori models integrating covariates to explain observed patterns of occupancy based on knowledge from the literature (Figure 2; Balestrieri, Mori, Menchetti, Ruiz‐Gonzalez, & Milanesi, 2018; Caryl, Quine, & Park, 2012; Zub et al, 2018). The ranking of candidate models was conducted using Akaike information criterion (AIC) corrected for sample size by calculating their Akaike weights (∆AIC; Burnham, Anderson, & Huyvaert, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Despite their historical decline being driven by persecution, there has been little research into how to minimize future human-wildlife conflict. Existing research on small carnivore conservation in Europe typically focuses on large-scale modelling of occurrence (Balestrieri et al 2019, Zub et al 2018, with limited fine-scale examination of populations and how fulfilling biological requirements in modern human modified environments may affect their recovery.…”
mentioning
confidence: 99%